Electric Motor Selection for Electric Go-Kart Development - ABU BAKAR, MUHAMMAD AZMAN BIN ABU BAKAR (Progress in Engineering Application and Technology, 2021)
The aim of this project is to select the suitable electric motor to replace the go-kart engine. The construction of this electric go- kart is to reduce the release of toxic and harmful gases released from the combustion of engines using gasoline sources and the noise that came from the go-kart. The toxic gases released can cause adverse effects on the environment and the human respiratory system. Thus, the noise that came from the vehicle may harm the hearing people that drive it and people that around the area especially kids. By considering the actual go-kart engine power, we compare the electric motor with the go-kart engine. All the data and information on the electric motor will be collected to determine the best motor to be replace the engine that can be carried the load of the chassis and the driver. Therefore, the selection of the right electric motor will help the go-kart movement within a certain distance and the predetermined speed. This study uses no-load test, which is run the electric motor without any load and chassis. From this test, we able to measure the mechanical losses of the chosen electric motor. From the data had been measured, we can see the losses by plotting the graph.